PERKAWINAN CAMPURAN DALAM KAITANNYA DENGAN UNDANG-UNDANG NO. 6 TAHUN 2011 TENTANG KEIMIGRASIAN - Amalia, Rafika; Supasti Darmawan, Ni Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol. 02, No. 02, April 2013)
Mixed marriage is a general practice among people of Indonesia. This practice is a result of interactions by people with different nationalities. The Law of The Republic of Indonesia Number 1 Year 1974 concerning Marriage already include rules of mixed marriage but did not specify arrangements regarding the presence of foreign nationals involved marriage. The Law of The Republic of Indonesia Number 6 Year 2011 concerning Immigration which replaces The Law of The Republic of Indonesia Number 9 Year 1992 concerning Immigration, foreign nationals who perform mixed marriages with Indonesian citizen were recognized and also the ease of a residence permit.
Keywords: Mixed marriage, citizen, foreign nationals, immigration.